Navigating taboos and tension - McLean, Bianca Judith (Rhodes University, 2026)
This thesis explores how discourses surrounding sexual health and education are negotiated and disseminated by South African TikTok influencers within the context of Comprehensive Sexuality Education (CSE). It specifically examines the work of two prominent creators, Dr Mpume Zenda (@dr.gynae) and Khumo Masege (@kmhealingagain), who engage audiences on topics such as consent, LGBTQ+ issues, and reproductive health. Using a constructivist theoretical framework, grounded in the works of Foucault, Hall, and Connell, this research employs textual and multimodal analyses to unpack how these influencers construct and communicate meanings through their content. South Africa’s CSE framework provides a progressive foundation for addressing sexual health, yet structural inequalities, cultural taboos, and gaps in traditional education persist. TikTok, as an emerging digital platform, offers a unique site for interaction, accessibility, and community building, allowing influencers to challenge or reinforce dominant discourses on sexuality and gender. This study applies thematic and narrative analyses to the content of the selected influencers, examining how their personal and professional narratives intersect with broader cultural and social discourses. Additionally, audience engagement, including comments, QandA sessions, and live videos, is analysed to evaluate the impact of this digital education on users’ knowledge, attitudes, and behaviours. This thesis argues that while TikTok provides an inclusive and dynamic platform for sexual health education, it also presents significant challenges, including risks of misinformation, privacy concerns, and the perpetuation of certain normative frameworks. The findings highlight the potential of TikTok to complement traditional education systems, fostering dialogue and accessibility while underscoring the necessity for critical digital literacy and ethical content moderation. Ultimately, this research contributes to a deeper understanding of the role of digital platforms in reshaping public health communication in South Africa’s evolving socio-cultural landscape.
South African medical professionals’ construction of sex education on TikTok
Keywords: Uncatalogued